The application of heat stress to team sports: Football/soccer, Australian football and rugby - Slattery, K.; Coutts, A. J. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
This chapter addresses how an added heat stress affects football, Australian football and rugby players during both training and competition. Although these sports are typically played in the cooler winter months, players can still be exposed to hot conditions and this may affect health and performance. It is therefore important to understand how an increased thermal load influences the tactical, technical, physical and psychological constructs that contribute to team sport performance. A review of the literature shows that players modify their physical activity patterns in the heat. This preserves the capacity to maintain technical skills, tactical awareness and perform explosive, high-intensity efforts when required. Nonetheless, players should still be prepared to tolerate the heat from both a performance and health perspective. Practical recommendations for heat acclimatisation, hydration and cooling strategies are provided in line with the current research and each code`s respective heat policy. As the information to date on heat stress in football, Australian football and rugby is based on a relatively small number of studies, further investigation is required to confirm these initial findings, optimise performance in hot conditions and protect players from the adverse effects of heat stress.